DEGENERATIVE CERVICAL MYELOPATHY: A REVIEW OF CURRENT CONCEPTS - PINTO,EDUARDO MOREIRA (2020)
ABSTRACT Herbert von Luschka, a German anatomist, was the first to describe the developmental changes in the anatomical structures of the cervical spine. Degenerative cervical myelopathy (DCM) represents a collection of pathological entities that cause compression of the cervical spinal cord, resulting in a clinical syndrome typified by spasticity, hyperreflexia, pathologic reflexes, finger/hand clumsiness, gait disturbance and sphincter dysfunction. In the cervical spine, certain patients are more likely to have myelopathy due to a congenitally narrowed cervical spine canal. Degenerative changes are more common at C5 and C6 or C6 and C7 due to the increased motion at these levels. Additional contributors to canal narrowing are infolding of the ligamentum flavum, olisthesis, osteophytes, and facet hypertrophy. Myelopathy will develop in approximately 100% of patients with canal stenosis greater than 60% (less than 6 mm sagittal disc cord space). Classically it has an insidious onset, progressing in a stepwise manner with functional decline. Without treatment, patients may progress toward significant paralysis and loss of function. Treatment requires surgery with either anterior or posterior decompression of the area of narrowing, and probable fusion. Factors of a poor prognosis include symptoms lasting for more than 18 months, increased range of motion in the cervical spine, and female gender. In this study, we give an overview of the state-of-the-art in DCM, with a focus on the pathophysiology, clinical presentation, differential diagnosis, imaging evaluation, natural history, treatment options and complications. Level of evidence III; Review article.